Teori Belajar Aliran Psikologi Gestalt Serta Implikasinya Dalam Proses Belajar dan Pembelajaran - Abdurrahman Abdurrahman (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2015)
Gestalt psychology is a school of psychology that studies a phenomenon as a whole or totality, the data in Gestalt psychology called the phenomenon (symptom). phenomenon is the most basic data in Gestalt Psychology. In this case the Gestalt Psychology phenomenologi agree with the philosophy that says that an experience should be seen as neutral. In a phenomenon, there are two elements, namely the object and meaning. The object is something that can be described, after being caught by the senses, the object becomes an information and once we have given meaning to that object. Basic Principles of Gestalt is the interaction between the individual and the environment called the perceptual field. Prinsi-organizing principles are: Principle of proximity, Principle of similarity, Principle of objective, Principle of continuity, Principle of closure / principle of good form, Principle of figure and ground, Principle of isomorphism. Gestalt Theory Application In Education and Promotion are: Experience insight (insight); Meaningful learning (meaningful learning); Purposeful behavior (pusposive behavior); The principle of living space (life space); Transfer in Learning.